A randomised, placebo-controlled clinical trial with the α2/3/5 subunit selective GABAA positive allosteric modulator PF-06372865 in patients with chronic low back pain - Gurrell, Rachel; Dua, Pinky; Feng, Gang; Sudworth, Maria; Whitlock, Mark; Reynolds, David S.; Butt, Richard P. (Pain (Amsterdam), 2018)
The effect of PF-06372865, a subtype-selective positive allosteric modulator of the γ-aminobutyric acid type A (GABA A ) receptor, on chronic low back pain was investigated in a randomised, placebo- and active-controlled phase 2 clinical trial. The parallel treatment group trial consisted of a 1-week single-blind placebo run in the phase, followed by 4-week double-blind treatment. Patients were randomised to receive either PF-06372865, naproxen, or placebo twice a day for 4 weeks. The primary end point was the numerical rating score of low back pain intensity after 4 weeks of active treatment. Secondary end points included the Roland Morris Disability Questionnaire and the Hopkins Verbal Learning Test–Revised. The trial had predefined decision rules based on the probability that PF-06372865 was better than placebo. The study was stopped at the interim analysis for futility. At this time, a total of 222 patients were randomised and the mean PF-06372865 4-week response on the low back pain intensity was 0.16 units higher (worse) than placebo (90% confidence interval −0.28 to 0.60). There were small, statistically significant reductions in the delayed recall test score with PF-06372865, as measured by Hopkins Verbal Learning Test–Revised. The effects of naproxen were in line with expectations. PF-06372865 was well tolerated. The most common treatment-related adverse events in the PF-06372865 arm were somnolence (5 mild and 4 moderate), dizziness (2 mild and 3 moderate), and nausea (2 mild). Although the reason for the lack of analgesic effect is not completely clear, it may be a result of not achieving sufficient receptor occupancy to drive efficacy.